Analysis of Utilization of Traditional Medicine for the Treatment of Malaria among Rural Farmers in Abia State, Nigeria - G.O., Mbah; N.M., Ekweanya (International Journal of Environment, Agriculture and Biotechnology, 2019)
The study investigated the level of utilization of traditional medicine for treatment of malaria among rural households in Abia State, Nigeria. Specifically, the study described socio -economic characteristics of the respondents; ascertain the extent of utilization of traditional medicine among the respondents and determine the factors influencing level of usage of traditional medicine in the area. Data for the study were collected from (180) respondents using structured questionnaire and analyzed using both descriptive and inferential statistics. The result showed that 55.0% of the respondents were males, average age of 58.45 years, 81.2% were married and 45.0% had secondary education. The study further revealed that respondents had high access to medicinal plants from market (mean = 2.35) and traditional medical practitioners (mean = 2.36). Tobit regression result showed that coefficient of age, years of education, income and farming experience influenced access to traditional medicine at 1% probability level. The study concluded that there was moderate utilization of traditional medicine for treatment of malaria in the study area, and recommended ensuring appropriate information on traditional medicine efficacy for effective utilization by the farmers in the study area.